A comparison of the activity demands of elite and sub-elite Australian men's basketball competition - Scanlan, A.; Dascombe, B.; Reaburn, P. (Journal of Sports Sciences, 2011)
The purpose of the study was to describe the differences in the activity demands of sub-elite and elite Australian men's basketball competition. Ten elite (age 28.3 ± 4.9 years, mass 97.0 ± 13.9 kg, height 197.4 ± 8.3 cm) and 12 sub-elite (age 26.1 ± 5.3 years, mass 85.9 ± 13.2 kg, height 191.4 ± 7.6 cm) Australian basketball players participated in the study. Player activity was analysed using video-based time-motion analysis across multiple in-season matches. Customized analytical software was used to calculate player activity into frequencies, mean and total durations (s), and mean and total distances (m) for standing/walking, jogging, running, sprinting, low shuffling, high shuffling, and dribbling movements. Only movement frequency was calculated for jumping and upper body activity. Multivariate analysis of variance revealed that elite players performed significantly more total movement changes (P <0.001), and experienced greater activity workloads while jogging (P <0.01) and running (P <0.002). In contrast, sub-elite players performed significantly more standing/walking (P <0.023) and sprinting (P <0.003) activities. These data suggest that elite basketball competition requires a greater intermittent workload and more sustained activity demands, whereas sub-elite competition may involve greater bursts of activity and longer recovery periods. These differences are likely to reflect variations in player skill and fitness, as well as playing structure between playing standards.